THE CONTROL OF OPERATIONAL PARAMETERS TO GET AN EFFICIENT PERFORMANCE OF THE MAIN NET OF TRANSPORT AND DISTRIBUTION OF DRY NATURAL GAS OF CAMISEA I PROJECT - Aybar Chávez, Víctor Alfredo (2014)
Current piping systems for transportation and distribution of dry natural gas in the Camisea I, project, involve the movement of millions of cubic feet of natural gas daily. Their capacity and operational reliability affect the final consumers. Their adequate operation and performance allows obtaining an efficient use of this resource. The objective of this work is to demonstrate that, through the control of certain operational parameters (specifically, values of pressure and flow of gas consumption in key points of the system), it's possible to get an efficient performance of the net (represented by users fuel consumption of the compressor stations). All of this, assumes free access of the users, and complying with contractual conditions among the members that conform the value chain of gas market.